Assessment on the implementation of Islamic principles by gated communities in Shah Alam, Selangor - Sharifah Fadylawaty binti Syed Abdullah (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
The gated community (GC) housing development has received both good and bad reviews. It is good in terms of its higher density, maintenance of amenities, provision of community facilities, increased vehicle and pedestrian safety, and sense of community. However, it has been criticized for promoting social exclusion and homogeneity, reduction in street connectivity, crime, and fear of crime. Little has been done to relieve this paradox, which thus motivates this research to examine the Islamic perspective on the issue. To this end, this study identified the following Islamic principles as affecting GCs: 1) Social Interaction 2) Social Responsibility 3) Prevention of Harm 4) Circulation System and 5) Right of Way / Right to Passage. We then assessed the application of these five (5) Islamic principles on seven (7) GCs in Shah Alam using convenience sampling. This study employed both quantitative and qualitative methodologies with the descriptive and content analysis to achieve the research objectives. The finding indicated that two (2) Islamic principles namely the Prevention of Harm and Circulation System were successfully implemented whereas the remaining three (3) principles, which are Social Interaction, Social Responsibility, and Right of Way were partially implemented in the study areas. We then recommended best practices of GCs from the Islamic perspectives. Among the recommendations are to nurture the culture of civic engagement among residents as well as empower the competency and integrity of the guards in improving the GCs' safety.